Facial expression modifies female body perception. (February 2023) - Noori, Farahnaz; Schofield, Heather; Summerscales, Lorna; Guo, Kun
The judgment of female body appearance has been reported to be affected by a range of internal (e.g., viewers' sexual cognition) and external factors (e.g., viewed clothing type and colour). This eye-tracking study aimed to complement previous research by examining the effect of facial expression on female body perception and associated body-viewing gaze behaviour. We presented female body images of Caucasian avatars in a continuum of common dress sizes posing seven basic facial expressions (neutral, happiness, sadness, anger, fear, surprise, and disgust), and asked both male and female participants to rate the perceived body attractiveness and body size. The analysis revealed an evident modulatory role of avatar facial expressions on body attractiveness and body size ratings, but not on the amount of viewing time directed at individual body features. Specifically, happy and angry avatars attracted the highest and lowest body attractiveness ratings, respectively, and fearful and surprised avatars tended to be rated slimmer. Interestingly, the impact of facial expression on female body assessment was not further influenced by viewers' gender, suggesting a 'universal' role of common facial expressions in modifying the perception of female body appearance.